Bacteria‐Based Production of Thiol‐Clickable, Genetically Encoded Lipid Nanovesicles. (23rd April 2019) - Royes, Jorge; Ilioaia, Oana; Lubart, Quentin; Angius, Federica; Dubacheva, Galina V.; Bally, Marta; Miroux, Bruno; Tribet, Christophe
Abstract: Despite growing research efforts on the preparation of (bio)functional liposomes, synthetic capsules cannot reach the densities of protein loading and the control over peptide display that is achieved by natural vesicles. Herein, a microbial platform for high‐yield production of lipidic nanovesicles with clickable thiol moieties in their outer corona is reported. These nanovesicles show low size dispersity, are decorated with a dense, perfectly oriented, and customizable corona of transmembrane polypeptides. Furthermore, this approach enables encapsulation of soluble proteins into the nanovesicles. Due to the mild preparation and loading conditions (absence of organic solvents, pH gradients, or detergents) and their straightforward surface functionalization, which takes advantage of the diversity of commercially available maleimide derivatives, bacteria‐based proteoliposomes are an attractive eco‐friendly alternative that can outperform currently used liposomes. Abstract : Eine Bakterienfabrik zur Produktion proteinbeladener, lipidischer Nanovesikel die mit einer anpassbaren, Thiol‐klickbaren Poylpeptidcorona dekoriert sind, wurde entwickelt. Dieses Verfahren bietet eine umweltverträgliche Alternative zu sonst verwendeten Methoden, da es Liposomen mit geringer Größendispersität ohne die Erfordernis von Tensiden oder organischen Lösungsmitteln produziert.